The Influence of Using the Shopeepaylater Payment Feature on Impulse Buying Behavior - Azzindani, M. Nabil; Tayo, Yanti; Susanto, Tri (Peneliti.net, 2024)
The research entitled “The Effect of Using the ShopeePayLater Payment Feature on Impulse buying Behavior” is a quantitative study that aims to determine the effect of using the ShopeePayLater payment feature on impulse buying behavior. This study uses a survey method. The sampling technique in this study used purposive sampling technique. The data collection technique used a questionnaire which was processed with SPSS. It is hoped that this research will be useful for developing theories related to impulse buying behavior and the use of ShopeePaylater. As well as being a source of information and adding insight so that you can be wiser in using payment methods. Apart from being a reference for further research, this research is also useful as an information provider for ShopeePaylater product and service developers. Based on the results of the study, it shows that there is an effect of the ShopeePayLater payment method on the impulse buying behavior of ShopeePayLater users of Singaperbangsa University students. The reason is because the ease of the transaction process and supported by attractive promos, such as free shipping, discounted prices, and cashback promos, can easily attract them to make purchases. This is included in irrational purchases or without thinking about the use value of the products they buy. Suggestions for ShopeePayLater users to be wiser and consider carefully the function/usefulness of the items they will buy. Should buy goods that are really needed in order to avoid impulse buying behavior.